Assessment of Wearable Virtual Reality Technology for Visiting World Heritage Buildings: An Educational Approach. (October 2018) - Fonseca, David; Navarro, Isidro; de Renteria, Isabela; Moreira, Fernando; Ferrer, Álvaro; de Reina, Oriol
The main aim of this study is to assess the spatial perception of historical world heritage buildings using wearable technologies in an educational framework. The proposal seeks to complement the real experience of visiting the Casa Batlló Museum, an emblematic space (1904–1906, Antonio Gaudí, Barcelona). The main innovative feature of the project is focused on the usability assessment of the video-guide indoor location-based system. The article addresses the first phase of a more complex project, analyzing the behavior of architecture students previously trained in modeling of complex buildings, in order to improve the system for a second phase that will be developed with students with special needs. Using an indoor location system for watching multimedia contents, we can improve the access, the visit, and the spatial perception of historical places for all kinds of students, with or without any special requirements. The results show a lack of usability of the system, especially due to the design of the mobile interface and to some loss of synchronization between the student position and the multimedia contents. However, the students have a better understanding of the museum's characteristics because of multimedia content, as a clear improvement compared with the classic audio-guide.